Trajectories of mental health before and after old-age and disability retirement: a register-based study on purchases of psychotropic drugs - Mikko Laaksonen; Niina Metsä-Simola; Pekka Martikainen; Olli Pietiläinen; Ossi Rahkonen; Raija Gould; Timo Partonen; Eero Lahelma (Nordic Association of Occupational Safety and Health (NOROSH), 2012)
OBJECTIVES: Retirement from paid work is a major life event facing increasingly large numbers of people in the coming years. We examined trajectories of mental health five years before and five years after old-age and disability retirement using data on purchases of psychotropic drugs. METHODS: The study included all employees from the City of Helsinki, Finland, retiring between 2000-2008 due to old age (N=4456) or disability (N=2549). Purchases of psychotropic drugs were analyzed in 20 3-month intervals before and after retirement using graphical methods and growth curve models. RESULTS: Old-age retirement was unrelated to purchases of psychotropic drugs. Among disability retirees, psychotropic medication tripled before retirement. The average increase was 0.95 [95% confidence interval (95% CI) 0.73-1.16] daily defined doses (DDD) 5-1.5 years before retirement; from 1.5 years until retirement it was 5.68 DDD (95% CI 5.33-6.03) for each 3-month interval. After disability retirement, purchases of antidepressants decreased on average by 0.40 DDD (95% CI 0.57-0.23) for each 3-month interval, those of hypnotics and sedatives increased by 0.30 DDD (95% CI 0.12-0.47), and no changes were seen for other psychotropic drugs. The changes before and after retirement were largest among those who retired due to mental disorders and those whose retirement had been granted as temporary. CONCLUSIONS: While no overall decrease in psychotropic medication after retirement was observed, purchases of antidepressants decreased after disability retirement. Long-term trajectories suggest that disability retirement might be prevented if mental health problems were tackled more efficiently earlier in the pre-retirement period.